Progress of Biomarkers in Diagnosis of Bone Metastases of Lung Cancer - Chao MENG; Chuanhao TANG; Jun LIANG (Chinese Journal of Lung Cancer, 2018)
Bone is one of the most metastatic sites of advanced malignant tumors. With the continuous improvement of diagnosis and treatment of malignant tumors, the survival time of patients is prolonged and incidence of bone metastases also increases. Lung cancer is the leading cause of cancer-related mortality worldwide. It is estimated that the incidence of bone metastases in patients advanced lung cancer is about 30%-40%. The traditional diagnosis of bone metastases in lung cancer is based on clinical symptoms, X ray, computed tomography (CT), magnetic resonance imaging (MRI) and pathology. Recently, a large number of exploratory studies have reported blood biomarkers as indicators of bone metastasis screening and efficacy evaluation. In this review, we summarize the progress of biomarkers in diagnosis of bone metastases of lung cancer.